Maternal stimulation and early child development in sub-saharan Africa: evidence from Kenya and Zambia - Silas Onyango; Patricia Kitsao-Wekulo; Nelson Langat; Kenneth Okelo; Dawn E. Murdock; Jürg Utzinger; Günther Fink (BMC, 2023)
Abstract Background Despite major improvements in child survival over the past decade, many children in low and middle-income countries (LMICs) remain at risk of not reaching their developmental potential due to malnutrition, poor health, and a lack of stimulation. Maternal engagement and stimulation have been identified as some of the most critical inputs for healthy development of children. However, relatively little evidence exists on the links between maternal stimulation and child development exists in sub-Saharan Africa (SSA). This current paper aims to identify the associations between maternal stimulation and child development in Kenya and Zambia, as well as the activities that are most predictive of developmental outcomes in these settings. Methods We conducted a descriptive study using data from a prospective study in Kenya and Zambia. The study included three rounds of data collection. Children were on average 10 months old in round one, 25 months old in round two, and 36 months old in round three. The primary exposure variable of interest was maternal stimulation activities, which we grouped into cognitive, language, motor, and socio-emotional activities. The outcome of interest was child development measured through the Third Edition of the Ages and Stages Questionnaire (ASQ-3). Linear regression models were used to estimate the associations between overall maternal stimulation and domain-specific maternal stimulation and child development across the three rounds of the survey. Results Higher maternal stimulation scores were associated with higher ASQ scores (effect size = 0.25; 95% CI: 0.19, 0.31) after adjusting for other confounders. For domain specific and child development (ASQ scores), the largest effect size (ES) was found for language stimulation (ES = 0.15) while weakest associations were found for socio-emotional domain activities (ES= -0.05). Overall maternal stimulation was most strongly associated with gross motor development (ES = 0.21) and the least associated with problem-solving (ES = 0.16). Conclusion Our study findings suggest a strong positive link between maternal stimulation activities and children's developmental outcomes among communities in poor rural settings. Trial registration NA (not a clinical trial).